Periostin upregulates the effector functions of eosinophils - Noguchi, Toru; Nakagome, Kazuyuki; Kobayashi, Takehito; Uchida, Yoshitaka; Soma, Tomoyuki; Nakamoto, Hidetomo; Nagata, Makoto (Journal of allergy and clinical immunology, 2016)
Eosinophils were obtained from healthy volunteers or allergic subjects with allergic rhinitis, and their adhesion to periostin or vascular cell adhesion molecule (VCAM)-1 was measured using residual eosinophil peroxidase assays (see this article's Methods section in the Online Repository at www.jacionline.org). [...]the viability after 48-hour culture was much decreased to about 40% to 60% (Fig E1; 46.6% [without stimulation], 66.8% [+IL-5], or 47.0% [+periostin]). [...]in this study, we incubated eosinophils for 24 hours for cytokine measurement.